HUNIAN DARURAT KEPADA KORBAN BENCANA ALAM YANG TERKENA GEMPA BUMI DI DESA CIPUTRI KECAMATAN PACET CIANJUR JAWA BARAT - Edi Sumatirta; Abu Naim; Helmas Septiyo Hadi; Sisca Wulandari; Yogi Priyo Istiyono; Faisal Kemal (Jurnal Abdimas Bina Bangsa, 2023)
The earthquake and landslide that occurred on November 21, 2022 at 13:21:10 WIB in Cianjur Regency, West Java Province is one of the natural disasters that occurred in Indonesia in 2022. Based on information obtained from the Head of the National Disaster Management Agency (BNPB) Suharyanto (2022), until November 2022 Indonesia was hit by around 3,207 natural disasters. Of these, 95 percent are hydrometeorological disasters such as floods to landslides. The purpose of this community service is to carry out community service activities to help victims of natural disasters in Ciputri Village, Pacet District, Cianjur, West Java by establishing emergency shelters so that local people get proper rest and other needs. Strategic target audiences to be involved in this community service program are communities affected by disasters, lecturers, students and a team of volunteers from UNIMAR